2011
DOI: 10.1186/1471-2288-11-130
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of loss to follow-up information in randomised controlled trials with time-to-event outcomes: a literature survey

Abstract: BackgroundTo assess the reporting of loss to follow-up (LTFU) information in articles on randomised controlled trials (RCTs) with time-to-event outcomes, and to assess whether discrepancies affect the validity of study results.MethodsLiterature survey of all issues of the BMJ, Lancet, JAMA, and New England Journal of Medicine published between 2003 and 2005. Eligible articles were reports of RCTs including at least one Kaplan-Meier plot. Articles were classified as "assessable" if sufficient information was av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 21 publications
0
23
0
1
Order By: Relevance
“…[77][78][79][80][81][82] LTFU introduces bias if the characteristics of participants LTFU differ between the randomized groups and the characteristics that differ are related to the trial's outcomes, especially if the proportion of participants LTFU differs between treatment groups. [77][78][79][80][81][82] For example, patients who are sicker at baseline are more likely to experience worsening of their condition; worsening may lead to withdrawal from the trial and the patient may die. Both worsening and death may be important outcomes in the trial and, if missing, will result in the trial giving an incomplete report of the true picture of what happens to patients with the condition.…”
Section: Discussionmentioning
confidence: 99%
“…[77][78][79][80][81][82] LTFU introduces bias if the characteristics of participants LTFU differ between the randomized groups and the characteristics that differ are related to the trial's outcomes, especially if the proportion of participants LTFU differs between treatment groups. [77][78][79][80][81][82] For example, patients who are sicker at baseline are more likely to experience worsening of their condition; worsening may lead to withdrawal from the trial and the patient may die. Both worsening and death may be important outcomes in the trial and, if missing, will result in the trial giving an incomplete report of the true picture of what happens to patients with the condition.…”
Section: Discussionmentioning
confidence: 99%
“…Authors implementing our suggested methods may be challenged by the fact that many trials either do not clearly report the number or the reasons of participants with missing data [14].…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the reason, the participants who drop out or who are lost to follow-up represent an atypical subgroup. 6,7,11 The systematic differences between the discontinuers and continuers threaten the credibility as well as the generalizability of the findings. 2 Many losses to follow-up particularly increase the possibility of a type-2 error (i.e., false-negative result), undermining the study power.…”
Section: Methodological Impact Of Loss To Follow-upmentioning
confidence: 99%
“…While excluding these patients may make the study less generalizable, including the patients poses a potential risk to the completeness of the data. Including a "run-in" or "wash-out" period in clinical trials 11,16 in which patients complete 1-2 visits before inclusion in the study, can help differentiate compliant from noncompliant participants. Further, during the runin period, collecting feedback on the intervention burden (i.e., issues related to the intervention that may affect adherence and compliance, such as injections or multiple trips to hospital) can assist to further resolve the noncompliance issue.…”
mentioning
confidence: 99%